2019
DOI: 10.21203/rs.2.12688/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Psychological Distress and Associated Factors among Adult Tuberculosis Patients Attending Public Health Institutions in Dire Dawa and Harar Cities, Eastern Ethiopia

Abstract: Background In developing countries the prevalence of psychological distress was higher among tuberculosis patients. Patients with tuberculosis infection were more prone to psychological distress than peoples without tuberculosis. However, little studies were conducted in on psychological distress among tuberculosis patients in Ethiopia, particularly in Eastern Ethiopian public health institution. Methods Institution-based cross-sectional study design was conducted. Based on the TB burden, four hospitals and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The subgroup analysis based on the continent where the review was done showed a signi cant difference in the average prevalence of alcohol use disorder among tuberculosis patients. The average prevalence of AUD in tuberculosis patients was higher in Asia and Europe;37% (11, 12, 17, 25, 35-38, 41-44, 47, 52) than the prevalence in US ; 24% (11,36) and Africa ; 24% (13,15,33,34,39,40,45,46,(48)(49)(50)(51)53). This was supported by earlier studies (66).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The subgroup analysis based on the continent where the review was done showed a signi cant difference in the average prevalence of alcohol use disorder among tuberculosis patients. The average prevalence of AUD in tuberculosis patients was higher in Asia and Europe;37% (11, 12, 17, 25, 35-38, 41-44, 47, 52) than the prevalence in US ; 24% (11,36) and Africa ; 24% (13,15,33,34,39,40,45,46,(48)(49)(50)(51)53). This was supported by earlier studies (66).…”
Section: Discussionsupporting
confidence: 64%
“…The average prevalence of AUD was 36% in studies that do not report the assessment tool for AUD (35,36,38,(40)(41)(42)(43)50) higher than the prevalence in studies that utilized AUDIT (26%) (11,12,15,17,25,34,(44)(45)(46)(47)(48)(49)(51)(52)(53). This could happen due to the possibility of inclusion of mild levels of alcohol use and the overestimation of AUD in studies that did not report the measurement tool.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations